Protective and therapeutic potentials of HDL and ApoA1 in COVID-19 elderly and chronic illness patients - AbdelHafez, Mohamed Aly (Bulletin of the National Research Centre, 2022)
Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for coronavirus disease-2019 (COVID-19). Elderly subjects, obese, and patients with chronic illnesses, are the most affected group. HDL has pleiotropic physiological functions that are affected with alteration(s) in its structure. Main text Inflammation whether septic, immune, or other affects HDL structure and function. COVID-19 is associated with systemic immune-inflammation due to cytokine surge. Viral interaction with erythrocytes and hemoglobin-related compounds (may cause anemia and hypoxia) and other factors may affect HDL function. Trials have been conducted to resume HDL functions using peptide preparation, nutritional, and herbal elements. Conclusions In this review article, I’ll discuss the use of reconstituted HDL (rHDL), Apo-A1 mimetic peptide D-4F, ω-3 polyunsaturated fatty acids, and the powdered roots and/or extract of Saussurea lappa (costus) to avoid comorbidity and mortality of COVID-19 in patients with chronic illness or elderly-age mortality.